Noninvasive diagnosis of pulmonary hypertension with hyperpolarised 129Xe magnetic resonance imaging and spectroscopy - Elianna A. Bier; Fawaz Alenezi; Junlan Lu; Ziyi Wang; Joseph G. Mammarappallil; Bryan O'Sullivan-Murphy; Alaattin Erkanli; Bastiaan Driehuys; Sudarshan Rajagopal (ERJ Open Research, 2022)
Background The diagnosis of pulmonary hypertension (PH) remains challenging. Pre- and post-capillary PH have different signatures on noninvasive 129Xe gas-exchange magnetic resonance imaging (MRI) and dynamic MR spectroscopy (MRS). We tested the accuracy of 129Xe MRI/MRS to diagnose PH status compared to right heart catheterisation (RHC). Methods 129Xe MRI/MRS from 93 subjects was used to develop a diagnostic algorithm, which was tested in 32 patients undergoing RHC on the same day (n=20) or within 5 months (42±40 days) (n=12). Three expert readers, blinded to RHC, used 129Xe MRI/MRS to classify subjects as pre-capillary PH, post-capillary PH, no PH and no interstitial lung disease (ILD), or ILD. Results For pre-capillary PH, 129Xe MRI/MRS diagnostic accuracy was 75% (95% CI 66–84) with a sensitivity of 67% (95% CI 54–79) and a specificity of 86% (95% CI 75–96); for post-capillary PH accuracy was 69% (95% CI 59–78) with sensitivity of 54% (95% CI 34–74) and specificity of 74% (95% CI 63–84). The model performed well in straightforward cases of pre-capillary PH but was less accurate in its diagnosis in the presence of mixed disease, particularly in the presence of ILD or combined post- and pre-capillary PH. Conclusion This study demonstrates the potential to develop 129Xe MRI/MRS into a modality with good accuracy in detecting pre- and post-capillary PH. Furthermore, the combination of 129Xe dynamic MRS and gas-exchange MRI uniquely provide concurrent, noninvasive assessment of both haemodynamics and gas-exchange impairment that may aid in the detection of PH.